Experimental salt marsh islands: A model system for novel metacommunity experiments. (5th November 2017) - Balke, Thorsten; Lõhmus, Kertu; Hillebrand, Helmut; Zielinski, Oliver; Haynert, Kristin; Meier, Daniela; Hodapp, Dorothee; Minden, Vanessa; Kleyer, Michael
Abstract: Shallow tidal coasts are characterised by shifting tidal flats and emerging or eroding islands above the high tide line. Salt marsh vegetation colonising new habitats distant from existing marshes are an ideal model to investigate metacommunity theory. We installed a set of 12 experimental salt marsh islands made from metal cages on a tidal flat in the German Wadden Sea to study the assembly of salt marsh communities in a metacommunity context. Experimental plots at the same elevation were established within the adjacent salt marsh on the island of Spiekeroog. For both, experimental islands and salt marsh enclosed plots, the same three elevational levels were realised while creating bare patches open for colonisation and vegetated patches with a defined transplanted community. One year into the experiment, the bare islands were colonised by plant species with high fecundity although with a lower frequency compared to the salt marsh enclosed bare plots. Initial plant community variations due to species sorting along the inundation gradient were evident in the transplanted vegetation. Competitive exclusion was not observed and is only expected to unfold in the coming years. Our study highlights that spatially and temporally explicit metacommunity dynamics should be considered in salt marsh plant community assembly and disassembly.